Model-based controls for integrated shading and UFAD control: Report on initial studies - Brian E. Coffey; Eleanor S. Lee (2011)
Methods and initial results are described for model-based controls with offline optimization for integrated shading and UFAD control for an office building in New York. Two cases are studied through lookup-table calculation and annual simulation of the resulting controllers: one case with interior blinds, the other case with exterior blinds. The interior blind case was found to reduce HVAC energy by 5% over a simple baseline control, and the exterior blind case produced a 5.6% HVAC energy savings over the baseline. Further investigations and case studies are planned.
Keywords: cloud computing; integrated controls; Model predictive control (MPC); offline optimization; shading and HVAC controls